Sintesis Dan Sifat Magnetik Komposit BaFe12O19/ZnO Terhadap Aplikasi Elektronik Media Perekam Dan Absorben - Veryyon Harahap; Veryyon Harahap; Sondang Sidabutar (FORUM ILMIAH KESEHATAN, 2020)
The purpose of this study was to synthesize BaFe12O19 / ZnO composites and use them as electronic applications for recording and absorbent media. Synthesis of Barium hexaferrite (BaFe12O19) using the Wet Milling method, with toluene media, while the ZnO Synthesis uses the coprecipitation method on powder. BaFe12O19 as a matrix and Zinc Oxide as a filler which is used as the main raw material for making composites. The results of Barium M-Ferrit and zinc oxide milling were mixed using wet milling with toluene media for 10 minutes and dried for half an hour at 200 oC. XRD (x-ray diffraction) results using full analysis, showed that the BaFe12O19 / ZnO composite was successfully synthesized. The crystal structure of Barium Hexaferrite is hexagonal and the peaks indicate single phase, each of the lattice parameters being BaFe12O19 a, b = 5.89 Å, c = 2.19 and spacegroup P63 / mm (194). The crystal structure of ZnO is hexagonal with lattice parameters a, b = 3.25 Å, b = 5.20 Å spacegroup P63mc (No.186) which is the wurtzite phase. The result of software match analysis shows that the percentage ratio of ZnO and BaFe12O19 atoms in this composite is the addition of ZnO mass by 50%, 75% has two phases, namely the ZnO and BaFe12O19 phases which show a heterogeneous structure with a hexagonal crystal structure. The morphology of the SEM photos shows that the barium hexaferrite grains are flat hexagonal in micron scale covered with ZnO. The VSM (Vibrating Sample Magnetometer) results showed that the magnetic properties of BaFe12O19 powder were obtained (Ms) magnetic saturation of 54.02 emu / g, (Mr) magnetic remanence 33.05 emu / g, (Hcj) coercivity 2941 Oe and (BHmax) product energy of 191 kGOe. Keywords: barium hexaferrite; zinc oxide; composite; coercivity; remanence ABSTRAK Tujuan penelitian ini adalah mensintesis komposit BaFe12O19/ZnO dan pemanfaatannya sebagai aplikasi elektronik media perekam dan absorben. Sintesis Barium heksaferit (BaFe12O19) menggunakan metode Wet Milling, dengan media toluene, sedangkan Sintesis ZnO menggunakan metode kopresipitasi pada powder. BaFe12O19 sebagai matriks dan Zinc Oxide sebagai filler yang digunakan sebagai bahan baku utama untuk pembuatan komposit. Hasil miling Barium M-Ferrit dan zinc Oxide dicampur menggunakan wet milling dengan media touluene selama 10 menit dan dikeringkan selama setengah jam pada suhu 200 oC. Hasil XRD (Difraksi sinar-x) menggunakan analisis macth, menunjukkan bahwa komposit BaFe12O19/ZnO telah berhasil disintesis. Struktur Kristal Barium Heksaferit adalah hexagonal dan puncak menunjukkan single fase, masing-masing parameter kisi adalah BaFe12O19 a,b = 5.89 Å, c = 2.19 dan spacegroup P63/mm (194). Struktur kristal ZnO adalah hexagonal dengan parameter kisi adalah a,b = 3.25 Å, b = 5.20 Å spacegroup P63mc (No.186) yang merupakan fase wurtzite. Hasil analisis software match menunjukkan bahwa perbandingan persentase atom ZnO dan BaFe12O19 pada komposit ini adalah penambahan massa ZnO 50%,75% memiliki dua fasa yaitu adanya fasa ZnO dan BaFe12O19 yang menunjukkan struktur heterogen dengan struktur kristal hexagonal. Morfologi hasil foto SEM menunjukan bahwa butir barium heksaferit berbentuk flat heksagonal dalam skala mikron yang ditutupi ZnO. Hasil VSM (Vibrating Sample Magnetometer) didapatkan nilai sifat magnet Serbuk BaFe12O19 didapatkan (Ms) magnet saturasi 54.02 emu/g, (Mr) magnet remanen 33.05 emu/g, (Hcj) koersivitas 2941 Oe dan (BHmax) energi produk 191 kGOe. Kata kunci: barium hexaferrite; zinc oxide; komposit; koersifitas; remanensi